P065 Altered B cell expansion and maturation in Crohn's disease. (30th January 2023) - Kappel-Latif, S; Kotagiri, P; Schuld, G; Schlager, L; Walterskirchen, N; Schimek, V; Jobst, J; Murthy, S; Messner, B; Lyons, P A; Oehler, R; Bergmann, M; et al.
Abstract: Background: One of the hallmarks of Crohn's disease (CD) is mesenteric thickening, accompanied by enlarged draining lymph nodes (LNs) in the affected areas. Descriptive studies imply that lymphatic architecture is altered in affected areas. Additionally, an altered IgA and IgG response towards commensal bacteria in CD patients compared to healthy controls has been described. Thus, we set out to investigate the B cell response in draining lymph nodes of patients with CD undergoing surgery. Methods: We prospectively collected draining lymph nodes and serum samples in patients with Crohn's disease during intestinal resections. LNs of affected and adjacent unaffected intestinal segments were processed for phenotyping by flowcytometry (n=18) and B cell receptor (BCR) sequencing (n=24). Histological analysis was performed to investigate size and number of germinal centers in affected and unaffected areas (n=10). Serum samples were collected from patients with CD undergoing surgery (n=18), and healthy individuals (n=16). The study was approved by the local ethics committee (EK #1480/2016) and all patients prospectively gave their written informed consent to participate in the study. Results: Affected draining LNs showed a significantly increased fraction of CD45 + CD19 + B cells (p=0.0055) compared to unaffected LNs. Fractions of double negative B cells (p=0.0394) and plasmablasts (p=0.0126) were significantly increased, and memory B cells significantly decreased (p=0.0127) in affected draining lymph nodes, respectively. Histological analysis revealed no difference in the numbers of germinal centers per high power field, but a significantly increased germinal center size (p<0.001). BCR sequencing demonstrated a reduction in IGHA (p<0.001) and IGHE (p=0.031), and a significant increase in IGHG1/2 (p<0.001) in affected LNs compared to unaffected LNs. Analysis of somatic hypermutation of BCRs and diversity analysis showed no significant increase in somatic hypermutation in IGHG1/2, and diversity analysis indicated significant diversity in specificity. Serum IgA of patients with CD recognized a significantly greater fraction of commensals in CD patients, and IgG binding towards commensals was almost universally detectable in CD patients but absent in healthy controls. Conclusion: Our data indicate that a pathological IgG response in patients with severe disease is directed towards a broad set of antigens, most likely stemming from commensals. Additionally, expansion only at the site of inflammation may indicate a triggered immune response due to a leaky intestinal barrier. The relevance of pathological IgG antibodies on disease recurrence following surgery needs to be addressed in future studies.